Kajian C-Organik, N Dan P Humitropepts pada Ketinggian Tempat yang Berbeda di Kecamatan Lintong Nihuta - Ardian Halomoan Sipahutar; Posma Marbun; Fauzi Fauzi (Universitas Sumatera Utara, 2014)
This research aims to know the difference of level of C-Organic, N and P in Humitropepts atdifferent altitudes in sub-district of Lintong Nihuta. The study done in sub-district of LintongNihuta at altitudes of 1300 to > 1500 meters above sea level in September – November 2013. Theresults showed that the C-Organic and N-total of Humitropepts sub-district of Lintong Nihuta tendto rise along with the added altitude and tend to decrease when increasing the depth of the soil. Incontrast, P-available tends to decreases with increasing altitude and the moment we get tend toincrease the depth of the soil.Key words: c-organic, nitrogen, phosphate, humitropepts, altitude.